Biosurfactants’ multifarious functional potential for sustainable agricultural practices - Karamchandani, Bhoomika M.; Pawar, Ameya A.; Pawar, Sujit S.; Syed, Sahil; Mone, Nishigandha S.; Dalvi, Sunil G.; Rahman, Pattanathu K. S. M.; Banat, Ibrahim M.; Satpute, Surekha K. (Frontiers in Bioengineering and Biotechnology, 2022)
Increasing food demand by the ever-growing population imposes an extra burden on the agricultural and food industries. Chemical-based pesticides, fertilizers and high-breeding crop varieties are typically employed to enhance crop productivity. Overexploitation of chemicals and their persistence in the environment, however, has detrimental effects on soil, water and air which consequently disturb the food chain and the ecosystem. The lower aqueous solubility and high hydrophobicity of agrochemicals, pesticides, metals and hydrocarbons allows them to adhere to soil particles and therefore persist in the environment. Chemical pesticides such as organophosphate, organochlorine and carbamate are used regularly to protect agriculture produce. The hydrophobic pollutants strongly adhered to soil particles can be desorbed or solubilized through the use of biosurfactant/s (BSs) or BS producing and pesticide degrading microorganisms. Among different types of BSs; rhamnolipids (RL), surfactin and Mannosylerythritol lipids (MELs) have been explored extensively due to their broad-spectrum antimicrobial activities against several phytopathogens. Different isoforms of lipopeptide viz. iturin, fengycin, surfactin have also been explored to combat phytopathogens. The role of BS in designing and developing biopesticide formulations is an encouraging approach to protect our environment. Various functional properties such as wetting, spreading, penetration abilities and retention periods are improved in surfactant-based formulations. This review focuses on the use of diverse types of BSs and their source microorganisms in the solubilization, degradation and removal of pollutants from soil. Extensive efforts seem to be focused on discovering innovative antimicrobial potential of BSs to combat phytopathogens. Sparse literature discusses the actual interactions of BSs and pesticides. Nanoencapsulation of pesticide formulations is an innovative approach in minimizing the actual pesticide doses and direct exposure to the human, animals. Thorough research in the area of nano-based formulation is mandatory to design and develop powerful organic preparations. A better understanding of the role of BSs in pesticide solubilization and/or degradation by microorganisms would be valuable in reducing the negative impact of such chemicals, pollutants for sustainable agricultural practices.